PEMANFAATAN SUMBER AIR PEGUNUNGAN UNTUK MENGANTISIPASI KEKERINGAN PADA MUSIM KEMARAU UNTUK TANAMAN KUBIS(TO EXPLOIT MOUNTAIN WATER RESOURCE FOR ANTICIPATION DROUGHT AT DRY SEASON FOR CABBAGE) - Meinarti Norma S; Sodiq Jauhari (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2008)
Operational step for dry season anticipation among to take schedule in plant pattern at location which often affected El Nino, to evaluate rain characteristic, to evaluaete irrigation availability, to prepare irrigation infrastructure and exploit alternative water resources. Beginning step for to got time and plant pattern with climate data is CWB-Eto program simulation. In this activity, data is taked from climate data at Canggal, Temanggung 2006, cabbage agronomy data and content water data. The result of climate data observation and CWB-Eto program simulation show the rain with 100 mm occurred at January – April and November – December, while the 20 % lost yield occurred.When farmer plants cabbage at January – Mei and September – October. For anticipation drought, micro irrigation and micro climate modification will decrease lost yield. The farmer when he will plant cabbage at dry season must make micro climate among mulc and irrigation with three day one. When we compare between the result research FAO and at Canggal, so cabbage which at Canggal was in good condition. Cabbage production at Canggal was 1,1 kg/plant and cabbage production at the result FAO is between 1 – 1.7 kg / plant.